1981
DOI: 10.1016/0020-7292(81)90011-4
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent induced abortion in Benin City, Nigeria

Abstract: Induced adolescent abortion is a major cause of maternal and gynecologic death in the University of Benin Teaching Hospital, where 244 out of 349 such cases seen from January 1, 1974 to December 31, 1979 were reviewed. Ignorance and lack of contraceptive facilities were contributory factors. To deal with this problem that has been pervasive throughout Nigeria for the past decade, the authors advocate sex education, systematic dissemination of information for planned and conscientious parenthood as well as free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
3
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 4 publications
5
23
3
2
Order By: Relevance
“…With over 60% of the abortions being in the first trimester, it is no surprise then that greater than 70% of cases were done by dilatation and curettage which also supports previous findings on the subject 9,19 . The fact too that over 70% of these patients had had at least one previous termination of pregnancy may not be unexpected as studies have shown that despite the increasing rate of sexual activity amongst adolescents, there is a low rate of contraceptive use in our environment 26 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…With over 60% of the abortions being in the first trimester, it is no surprise then that greater than 70% of cases were done by dilatation and curettage which also supports previous findings on the subject 9,19 . The fact too that over 70% of these patients had had at least one previous termination of pregnancy may not be unexpected as studies have shown that despite the increasing rate of sexual activity amongst adolescents, there is a low rate of contraceptive use in our environment 26 .…”
Section: Discussionsupporting
confidence: 77%
“…The incidence was 27.4 per 1000 live births and 3.93% of gynaecological admissions. This is much lower than the finding in a similar study done in this centre 14 years ago 19 . This may be attributed to the presence of more alternative specialist clinics and private hospitals that offer care to the complicated cases or even to a decreased incidence of complications as abortionists acquire greater proficiency.…”
Section: Discussioncontrasting
confidence: 55%
“…About one-fifth of single women had been pregnant and the same proportion had had abortions. Some studies have indicated that abortion among single women is due to ignorance, lack of contraceptive facilities (Omu et al 1981) and an unwillingness to use contraceptives because of wrong information (Okonofua et al 1992). The most common reason for non-use of contraceptives in this study was fear of side-effects.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the women admitted for complications of induced abortion are teenagers (Ikechebelu and Okoli 2003;Omu et al 1981). An earlier study from this centre gave the incidence of induced abortion as 4/1,000 deliveries, with 71% of them 20 years or below and eight out of 10, nulliparous (Megafu and Ozumba 1991).…”
Section: Introductionmentioning
confidence: 99%